Physiological differences between two overlapped breeding Antarctic penguins in a global change perspective - D'amico, Veronica Laura; Coria, Néstor; Palacios, Maria Gabriela; Barbosa, Andrés; Bertellotti, Nestor Marcelo (Polar Biology)
Global change has affected the Antarctic Peninsula influencing the abundance of krill, one of the main preys of penguins. In areas where breeding penguin populations overlap, species with a more diverse diet have generally been less affected than krill-specialist species, which have shown population declines. Human activities can add to these changes, as penguins are sensitive to anthropic impacts such as contamination. Our objective was to assess whether selected physiological parameters of Adelie and Gentoo penguins reflect their contrasting population trends in a colony located at Punta Stranger (25 de Mayo Island/King George, South Shetland Islands) where they breed sympatrically. During 2012, we assessed the leukocyte profile, heterophil to lymphocyte ratio (H/L), erythrocytic nuclear abnormalities (ENAs), hematocrit, biochemical profile, and a measure of immune function (bacterial agglutination) in adults and chicks of both species. Higher values of ENAs, indicative of genotoxic damage caused by contaminants, are in accordance with a greater sensitivity to ongoing global changes by Adelie penguins. Levels of cholesterol and triglycerides strengthen this idea since individuals could be investing more resources in energy reserves to successfully cope with challenging environmental conditions during the breeding season. The remaining physiological parameters did not provide a clear picture. Furthermore, some results could be related to differences in diet. Gentoo show greater prey diversity than Adelie penguins, incorporating a richer parasite fauna, which could explain their higher heterophils and H/L. The physiological parameters measured here serve as baseline for a sustained monitoring of these rapidly changing populations. Further physiological variables, including stress hormone and indices of oxidative stress, remain to be assessed as potential indicators of population susceptibility to global change in this system. Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y ...